The komedya of international development in Camiguin island ethnographic stories on program impact and sustainability - Narros, Andres (Quezon City Ateneo de Manila University, 2014)
"There remains a lack of connection between existing standards of international development projects and the social and cultural complexities of rural Philippine communities where these projects are situated. This article attempts to supply the missing connection by discussing a case study in Camiguin Island in northern Mindanao, where a Spanish government-funded development program took place for fourteen years from 1990 to 2004. This study explores the community's perceptions of the program through an alternative ethnography, using the "archaeological approach" and the traditional play "komedya" as metaphor, to understand the correlations among project standards, local complexities, and project impact and sustainability."
Keywords: Community development; Patron-client system